NMDB and space weather forecasting - Gololobov, Petr Yu.; Starodubtsev, Sergey A.; Grigoryev, Vladislav G.; Zverev, Anton S. (2023)
From the creation of NMDB in 2007 and through the growth in the number of stations and the data accumulation, the ShICRA SB RAS group continuously have used its facilities. For the last years we have created a method for short-term forecasting of intense geomagnetic storms with an advance time 1-2 days. The probability of forecasting is around 80%. We have reported about the method in the previous NMDB: virtual symposium on cosmic ray studies with neutron detectors in 2020. The method is based on the global survey method that was developed in Yakutsk in 1960s and uses the world network of neutron monitors as a single multidirectional device. The method is intended to estimate hourly dynamics of cosmic ray anisotropy in free-space. Note that only with the NMDB creation we managed to implement it in real time mode. Now we started work on creating another method for space weather forecasting by measurements of cosmic ray fluctuations. For this purpose, we use 1-min data of NMDB. In the current report we present the first results of our investigation on forecasting of intense geomagnetic storms with Dst < -50 nT. The results obtained indicate the possibility of developing and implementing in real time a method for predicting strong geophysical manifestations of space weather on the basis of ground-based cosmic ray measurements.